‘Just a wee boy not cut out for prison’: Policy and reality in children and young people’s journeys through justice in Scotland: - Nolan, Deborah Ann (Criminology & criminal justice, 2018)
Youth Justice policy in Scotland, under the ‘Whole System Approach’ (WSA), progressively espouses maximum diversion, minimum intervention and the use of alternatives to custody wherever possible. Yet Scotland still has one of the highest imprisonment rates in Europe. To explore this discrepancy, this qualitative study used individual interviews and focus groups to document the experiences of 14 young males aged 16 and 17 in one Scottish young offenders’ institution on their journeys to custody. Their experiences reveal the significant challenges faced in understanding, navigating and complying with the justice system, and also indicate that the consistent implementation of WSA is problematic. The disconnection between the intentions of the WSA policy and the practical implementation means that these vulnerable young people are not fully benefiting from the WSA. This article therefore highlights important gaps between policy, practice and lived experience in youth justice in Scotland.